Spore six days a week! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Cooperative Agricultural Centre of Benin, in Houègbo, Benin, tells us that Spore, and other publications ordered from CTA, have been given pride of place in their information centre. 'Open six days a week, the centre runs a special Reading Club...